LAYANAN BIMBINGAN KELOMPOK MENGGUNAKAN TEKNIK MODELING UNTUK SELF EFFICACY SISWA KELAS XI SMK NEGERI 01 CIPONGKOR - Fauzi, Ahmad Anwar; Rohaeti, Euis Eti; Ningrum, Devy Sekar Ayu (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
This study aims to describe group counseling services using the modeling technique for students with low self-efficacy at SMKN 01 Cipongkor. The research design employed is a qualitative descriptive method. The subjects in this study were six eleventh-grade students at SMKN 01 Cipongkor. Data collection methods used were interviews, documentation, and observation. Data analysis techniques included data collection, data reduction, data presentation, and drawing conclusions. The results of the study revealed that group counseling services using the modeling technique were provided to students identified as having low self-efficacy and were carried out in four stages. Students responded very positively to the group counseling services using the modeling technique. The challenges faced by the guidance and counseling teacher during implementation were related to inadequate facilities and infrastructure. Students experienced an increase in self-efficacy after receiving group counseling services through the modeling technique. Based on these results, group counseling services using the modeling technique can be used as a reference for future researchers who wish to conduct studies on students’ self-efficacy levels.